The Economics of Microﬁnance - Armendáriz, Beatriz (The MIT Press, 2012)
"The microfinance revolution has allowed more than 150 million poor people around the world to receive small loans without collateral, build up assets, and buy insurance. The idea that providing access to reliable and affordable financial services can have powerful economic and social effects has captured the imagination of policymakers, activists, bankers, and researchers around the world; the 2006 Nobel Peace Prize went to microfinance pioneer Muhammad Yunus and Grameen Bank of Bangladesh. This book offers an accessible and engaging analysis of the global expansion of financial markets in poor communities. It introduces readers to the key ideas driving microfinance, integrating theory with empirical data and addressing a range of issues, including savings and insurance, the role of women, impact measurement, and management incentives. "